1994
DOI: 10.1037/0096-3445.123.3.264
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of language maintenance and language dominance in bilingual Hispanic immigrants.

Abstract: Spanish language tests of 801 Cuban and Mexican immigrants showed no evidence of language loss during 50 years of U.S. residence; a few years after immigration, their English vocabulary approximated that of English monolinguals. The critical-age hypothesis was not supported for the acquisition of English vocabulary when English schooling and language usage were controlled by multiple regression. Most Ss continued to speak about as much Spanish as English; but read, wrote, and heard (on television and radio) fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(83 citation statements)
references
References 38 publications
(58 reference statements)
6
76
1
Order By: Relevance
“…A matched subgroup analysis confirmed that the AOA effect on foreign accent ratings was not due to factors that were confounded with AOA as in previous research (e.g., Bachi, 1956;Bahrick et al, 1994;see Flege, 1998a). Two matched subgroups of 20 Korean participants each were established by selecting participants who differed in AOA but did not differ significantly in terms of how much education they had received in the United States, their length of residence in the United States, or their use of English and Korean.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…A matched subgroup analysis confirmed that the AOA effect on foreign accent ratings was not due to factors that were confounded with AOA as in previous research (e.g., Bachi, 1956;Bahrick et al, 1994;see Flege, 1998a). Two matched subgroups of 20 Korean participants each were established by selecting participants who differed in AOA but did not differ significantly in terms of how much education they had received in the United States, their length of residence in the United States, or their use of English and Korean.…”
Section: Discussionsupporting
confidence: 77%
“…However, this does not mean necessarily that the "age" effects presented so far can be attributed exclusively, or even primarily, to AOA. As mentioned earlier, AOA is typically confounded with other variables in studies examining large immigrant populations (see, e.g., Bachi, 1956;Bahrick et al, 1994). This study was no exception, for there was multi-collinearity among variables associated with the Korean participants' AOAs.…”
Section: Matched Subgroup Analysesmentioning
confidence: 79%
See 2 more Smart Citations
“…For instance, Bahrick and his colleagues (Bahrick, 1983(Bahrick, , 1984Bahrick & Hall, 1991;Bahrick, Hall, Goggin, Bahrick, & Berger, 1994) examined the very longterm retention of information learned during high school (Spanish vocabulary words; mathematical concepts; spatial maps) and concluded that if information is not learned well, it will be completely forgotten within 3-5 years. However, if it is adequately encoded, it will enter "permastore" and persist essentially undiminished across 50 years (Bahrick, 2000).…”
Section: Discussionmentioning
confidence: 99%